Isolation of antagonistic fungi from rhizospheres and its biocontrol activity against different isolates of soil borne fungal pathogens infected legumes - ERIYANTO YUSNAWAN; ALFI INAYATI; YULIANTORO BALIADI (Society for Indonesian Biodiversity, 2019)
Abstract. Yusnawan E, Inayati A, Baliadi Y. 2019. Isolation of antagonistic fungi from rhizospheres and its biocontrol activity against different isolates of soil borne fungal pathogens infected legumes. Biodiversitas 20: 2048-2054. Soilborne diseases caused by Rhizoctonia solani and Fusarium sp. are biotic limits for legume production. Biological controls offer environmental friendly control for these pathogens. This study aimed to isolate and screen Trichoderma from different rhizospheres and to obtain effective Trichoderma isolates to suppress in vitro growth of the soil borne pathogens. The antagonistic inhibitory activity was performed by dual culture method. Seven out of forty indigenous Trichoderma isolates collected from East Java, Indonesia effectively suppressed the growth of different fungal isolates, namely Rhizoctonia solani (R.s1), R. solani (R.s2) as well as Fusarium sp. which infected soybean and mung bean. In vitro study showed different suppression of the pathogens on dual culture tests. The seven isolates inhibited the growth of R. solani (R.s1), R.solani (R.s2) and Fusarium sp. ranging from 90.0 to 99.6%, 72.8 to 82.4%, and 67.9 to 90.8%, respectively. Isolate origin and genetic variability of Trichoderma played an important role in the antagonistic activity. The fast-growing of selected Trichoderma showed their abilities for space occupation and nutrition competition, which involved in the antagonistic activity. The mycelial growth of Trichoderma over pathogens showed hyperparasitism mechanism. In addition, coiling of Trichoderma over hyphal pathogens was observed during microscopic observation. The seven Trichoderma isolates, therefore, are promising as biological control agents against the soil borne fungi infected legumes.